(untitled) (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 1998)
This paper describes a set-theoretical argument for proving Strong Normalization (SN) for the systems of the so-called λ-cube. The argument is relatively simple and, moreover, flexible. It can be adapted to extensions of the systems considered, such as additional sorts, inductive types or sub-types.